2014
DOI: 10.1002/sia.5712
|View full text |Cite
|
Sign up to set email alerts
|

The high concentration and uniform distribution of diamond particles in Ni-diamond composite coatings by sediment co-deposition

Abstract: Ni‐diamond composite coatings with high concentration and uniform distribution of diamond particles were prepared by using sediment co‐deposition (SCD) technique from Watts‐type electrolyte without any additives. The surface and cross‐section morphology was evaluated by optical microscope (OM) and scanning electron microscopy (SEM). It was demonstrated that the Ni‐monolayer diamond composite coatings ~40 ± 5 µm was successfully prepared by the new developed setup for SCD technique. Using this new developed set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Therefore, the diamond content in Ni-W/diamond composite coatings prepared using the conventional electrodeposition is low, so that the hardness of diamond particles would make only a minor contribution to the hardness of the obtained coatings. We have previously demonstrated the preparation of composite coatings using SCD method 15 . Figure 1(a) shows the setup of SCD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the diamond content in Ni-W/diamond composite coatings prepared using the conventional electrodeposition is low, so that the hardness of diamond particles would make only a minor contribution to the hardness of the obtained coatings. We have previously demonstrated the preparation of composite coatings using SCD method 15 . Figure 1(a) shows the setup of SCD.…”
Section: Resultsmentioning
confidence: 99%
“…The bath composite and plating conditions are listed in Table 1 . We have previously demonstrated the preparation of composite coatings using SCD method 15 . Figure 1(a) shows the setup of SCD.…”
Section: Methodsmentioning
confidence: 99%
“…Temperatures are controlled throughout the process and generally ranged between 40 and 60 °C. (QIN et al, 2014;ZHOU et al, 2015) 6 | HEAT TREATMENT AFTER THE ELECTROPLATING Some authors have been reported improvements in adherence and mechanical properties of coatings through heat treatments after the deposition. Wang et al (2014) studied the heat treatment of Ni-W/nanocrystalline diamond deposited at stainless steel.…”
Section: Diamond Particles Characteristicsmentioning
confidence: 99%
“…Burkat et al have reported that the hardness of electrodeposited nickel increases up to 90% with the addition of 4.3 nm diamond particles in the nickel matrix [3] at a diamond content in the composites of only 0.65 wt.%. In the past, some studies reported on the incorporation of high volume fractions of micron-sized diamond particles in electrodeposited metal matrices [23,25,26]. The thermal conductivity of these metal-diamond composites could potentially be suitable for heat sink applications.…”
Section: Introductionmentioning
confidence: 99%